KEPRIBADIAN ANAK WANITA KARIER DI DESA PAGAR MERBAU III KECAMATAN LUBUK PAKAM KABUPATEN DELI SERDANG - Arnisah (Jurnal Bilqolam Pendidikan Islam, 2022)
A child's personality is an organized pattern of behavior and attitudes that can make a child a unique individual. The child's personality must be fostered through proper education towards a good personality by equipping a child with knowledge, both religious knowledge and general knowledge. This study aims to determine how the personality of career girls in Pagar Merbau III Village, Lubuk Pakam District. The method used in this study is a qualitative method with a descriptive narrative approach. The data collection technique of this research used observation, interview, and documentation techniques. From the results of this study, it can be concluded that the personality of career girls in Pagar Merbau III Village has a good personality. The obedience of career girls in Pagar Merbau III Village is good. They are used to doing obedience to Allah SWT by praying and reading the Koran. The honesty of career girls in Pagar Merbau III Village is good. They still go and come home from school on time even though they are not directly supervised by their parents. The character of the career girls in Pagar Merbau III Village is good. However, they have an individualistic attitude and rarely socialize with society